Digital narratives on climate, peace and security in the Philippines: an exploratory analysis - Carneiro, Bia; Ruscica, Giosue (2025)
This analysis leverages publicly available Facebook data to examine how climate change, socio-economic risks, and conflict are framed by policy-relevant stakeholders and media actors in the Philippines. Drawing on Digital Methods approaches, online issue mapping techniques were applied to detect how issues related to climate change and security emerge and evolve in online networked content. The brief summarizes initial, exploratory findings for a diagnostic assessment of the current ‘state of play’ regarding peace positive and climate action policy discourses in the Philippiness and provides a starting point for the development of evidence-based advocacy and engagement strategies.